2019
DOI: 10.1177/1747493019835335
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic disparities in hospital utilization in intracerebral hemorrhage

Abstract: Background and purpose There is evidence that racial and ethnic differences among intracerebral hemorrhage (ICH) patients exist. We sought to establish the occurrence of disparities in hospital utilization in the United States. Methods We identified ICH patients from United States Nationwide Inpatient Sample database for years 2006–2014 using codes (DX1 = 431, 432.0) from the International Classification of Diseases, 9th edition. We compared five race/ethnic categories: White, Black, Hispanic, Asian or Pacific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
(50 reference statements)
1
20
0
Order By: Relevance
“…40 Another study that identified 710,293 hospitalized intracerebral hemorrhage patients from the United States Nationwide Inpatient Sample database for the years 2006-2014 revealed that Hispanic Whites had greater utilization of palliative care, and hospice than non-Hispanic Blacks. 39 Furthermore, a retrospective study revealed considerable racial/ethnic disparities in the quality of palliative and endof-life care. Minorities were more likely than non-Hispanic Whites to experience potentially preventable medical encounters in the last month of life.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…40 Another study that identified 710,293 hospitalized intracerebral hemorrhage patients from the United States Nationwide Inpatient Sample database for the years 2006-2014 revealed that Hispanic Whites had greater utilization of palliative care, and hospice than non-Hispanic Blacks. 39 Furthermore, a retrospective study revealed considerable racial/ethnic disparities in the quality of palliative and endof-life care. Minorities were more likely than non-Hispanic Whites to experience potentially preventable medical encounters in the last month of life.…”
Section: Methodsmentioning
confidence: 99%
“…After searching almost fourthly-thousand citations, 284 articles were included in our study, of which 147 were manuscripts that directly addressed end-of-life and hospice care, palliative care, as well as advance care planning and directives that include non-Hispanic Blacks. 4 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations